Giải pháp phát triển hệ thống bảo đảm chất lượng bên trong theo tiếp cận TQM để quản lí chương trình đào tạo đại học tại Trường Đại học Xây dựng Hà Nội - Nguyễn , Trung Thành (Tạp chí Giáo dục, 2023)
The current context of educational integration requires each university to build and develop an internal quality assurance system. This article focuses on researching and proposing solutions to developing the internal quality assurance system for university training program management based on the total quality management - TQM approach at the Ha Noi University of Civil Engineering. Based on an approach related to quality assurance and TQM, using theoretical and practical research methods as well as researching the output of the training process, the study aims to propose 04 development solutions to the internal quality assurance system of university training program management includes: (1) Output standards of the training program; (2) System for ongoing and post-graduation controlling/monitoring of the quality of training programs; (3) Training program quality assessment system; (4) Feedback to continuously improve the quality of training programs. These solutions contribute to helping the School manage and control by keeping track of training program implementation, providing continuous feedback to help propose and make decisions on solutions to continuous improvement of training quality, in accordance with the quality culture philosophy of “mobilizing” all stakeholders in continuously improving training quality.